KONTRIBUSI KERAJAAN MUGHAL TERHADAP PERKEMBANGAN ISLAM DI ANAK BENUA INDIA - Nurcahya, Yan; Hambaliana, Dandie; Solehudin, Solehudin (Jazirah: Jurnal Peradaban dan Kebudayaan, 2024)
Consist The Mughal Empire, also known as the Moguls or Moghuls, was a state that ruled Afghanistan, Balochistan, and most of India between 1526 AD and 1857 AD. Mughal is the Indo-Aryan version of the word Mongol, as it was part of the Timurid dynasty from Central Asia. Officially the Mughal people were Muslims. In this period three great kings were formed: the Ottomans in Türkiye, the Shafavids in Persia, and the Mughals in India. The Mughals controlled the entire region, causing significant changes in the Islamic world. Babur was the first to establish an Islamic kingdom in India, and his son, Nashiruddin Humayun (1530-1539 AD), succeeded him. Muslims in India are considered a minority, and their influence is felt across various religions. Muslims were considered a minority within Islam, and their influence was further spread by Mughal rule. It was during this period that Islam spread and developed in the Indian Subcontinent. In terms of methodology, historical research is the study of various historical sources, both primary and secondary. From the paper presented, we can see the contribution of the Mughal Empire to the development of Islam in the Indian Subcontinent in various aspects at that time, including; Politics, Education, Science, Literature, Architecture, Technology and City Development.